2011
DOI: 10.1088/0953-8984/23/17/175004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of mixed lubrication with smooth particle post-processing

Abstract: A post-processing method for molecular dynamics (MD) simulations of friction based on the smooth particle approach is proposed, allowing--among other features--the introduction and evaluation of a solid-solid contact area arising due to direct asperity interaction. In order to illustrate the feasibility of this scheme, a large number of MD calculations of lubricated nanotribological systems with various asperity geometries and carefully selected numbers of lubricant molecules were carried out and analysed. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 52 publications
0
55
0
Order By: Relevance
“…The resulting load versus friction behaviour was then analysed to study these parameters affected the friction coefficient and the extrapolated friction force at zero load (Derjaguin offset). A smooth-particle-based evaluation method [240] was used to visualize the sliding interface between the two OFM layers. This allowed the definition and calculation of a dimensionless normalized sliding resistance area, which was then related to the Derjaguin offset.…”
Section: Friction Behaviourmentioning
confidence: 99%
“…The resulting load versus friction behaviour was then analysed to study these parameters affected the friction coefficient and the extrapolated friction force at zero load (Derjaguin offset). A smooth-particle-based evaluation method [240] was used to visualize the sliding interface between the two OFM layers. This allowed the definition and calculation of a dimensionless normalized sliding resistance area, which was then related to the Derjaguin offset.…”
Section: Friction Behaviourmentioning
confidence: 99%
“…Solhjoo and Vakis [16] defined the contact distance as being slightly larger than the first neighbor distance based on crystallographic packing factors. Eder et al [17] suggested that, in the case of an amorphous structure, a statistical value could be used for the definition of the contact distance, namely the radial distribution function.…”
Section: A Short Review Of Contact At the Atomic Scalementioning
confidence: 99%
“…Furthermore, in a system with amorphous structure, the peaks are by definition not related to any specific crystal structure, demonstrating the randomness of the atoms' positions in the system. For an amorphous system, Eder et al [17] suggested that a value slightly smaller than the first minimum in the g(r) plots can be assigned as the contact distance. In yet another approach to detect atoms at contact based on the potential energy of each atom, Solhjoo and Vakis [18] showed that surface atoms have higher potential energies than atoms in the bulk.…”
Section: A Short Review Of Contact At the Atomic Scalementioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a limited number of works on boundary lubrication by MD simulation that take the asperity contact with lubricant into account. Eder et al [16] proposed a smooth particle approach to define and calculate the asperity contact area and lubricant cavity volume. The influence of different shaped asperities and normal load on the contact area and friction force was discussed.…”
Section: Introductionmentioning
confidence: 99%